Comparison Study of Prime Services at Public Service Mall West Tanjung Jabung Regency and Jambi City - Fadillah, Nisaul; Elianda, Yunita; Hartono, Sigit (Universitas Muhammadiyah Sidoarjo, 2024)
This article discusses the comparison of the implementation of Excellent Service through Public Service Malls which are implemented at the West Tanjung Jabung Public Service Mall and the Jambi City Public Service Mall. The purpose of this research is to see the readiness of the government of West Tanjung Jabung and Jambi City in providing services to the community and to find out the perceptions of users of the Public Service Mall of West Tanjung Jabung Regency and Jambi City regarding the quality of public service Mall services. The theory used in this research is Excellent Service and Public Service. The research method used was using the Mix Method. The results of the analysis carried out are that the Jambi City Public Service Mall and West Tanjung Jabung Public Service Mall have been implemented well, but there are several obstacles such as the Jambi City Public Service Mall still does not have an elevator so it is still not adequate and disability friendly. Meanwhile, the West Tanjung Jabung Public Service Mall still lacks space, but the government will rebuild the building to meet service needs